MOG-IGG IN NMO AND NMO-LIKE DISORDERS. Issue 10 (9th September 2014) - Luppe, Sebastian; Waters, Patrick; Vincent, Angela; Robertson, Neil
Abstract : 40% of patients with an NMO-phenotype are seronegative for AQP4-IgG. Recent reports of antibodies against myelin-oligodendrocyte-glycoprotein(MOG) in NMO suggest an independent MOG-IgG disease. We compare the disease course, treatment and paraclinical results of 6 MOG-IgG+ vs. 41 AQP4+ patients. We collected serum and clinical information from 67 patients with NMO phenotypes. Serum samples were analysed for AQP4-IgG and MOG-IgG. 4F, 2M patients were MOG-IgG+ [32F:2M AQP4-IgG+]; none were positive for both antibodies. Mean-age-at-onset 27.6 years(14.7–45.6) MOG-IgG+ [41.6 yrs (3.8–77.2) AQP4-IgG+], mean disease duration 7.7 years (1.7–21.3) MOG-IgG+ [8.6 years (2.0–32.4) AQP4+], mean annualized relapse rate 0.7 (0.6–1.1)MOG-IgG [0.8 (0.1–2.3) AQP4-IgG+]. Mean EDSS at last follow-up was 3.0 (1.5–4.0) MOG-IgG+ [5.2 (1.5–8.0) AQP4-IgG+]. Patients with MOG-IgG+ related CNS disease exhibited a relapsing disease course and although recovery from repeated episodes of ON and LEM appears better than in AQP4-IgG+ disease, patients remain at risk of significant long-term disability.